Pengaruh Penggunaan Model Pembelajaran Open Ended Terhadap Hasil Belajar Siswa Dalam Pembelajaran Matematika Kelas V SDN 3 Purwawinangun - Vina; Cunandar, Dadang (Universitas Muhammadiyah Bangka Belitung, 2024)
The aim of this research is to find out what the mathematics learning outcomes of students in Class V of SDN 3 Purwawinangun are before and after using the Open Ended Learning Model. To find out whether there is an influence of using the Open Ended Learning Model on student learning outcomes in Class V SDN 3 Purwawinangun. The method in this research is Quantitative Experiment Design with a One-Group Pretest-Posttest design. The research population was all fifth grade students at SD Negeri 3 Purwawinangun, totaling 44 students. The sample was the VB class, totaling 23 students. The data collection technique uses ability tests on student learning outcomes in the form of a Pre-test and Post-test with 10 questions, observation and documentation. Based on the results of research and data analysis, it shows that learning using the Open Ended model has an influence on student learning outcomes in mathematics subjects at SDN 3 Purwawinangun. This is proven by obtaining the Sig hypothesis results. (2-tailed) = 0.000 < 0.005 then Ha is accepted. It can be concluded that the application of the Open Ended learning model influences student learning outcomes at SDN 3 Purwawinangun